Revisiting the connection between context and language from Hall to Jullien: A contribution to a real intercultural dialogue - Agostini, Bertrand; Persson, Sybille (Management international / International Management / Gestiòn Internacional, 2022)
This conceptual article offers an interdisciplinary journey from Edward T. Hall to François Jullien, from context to language, and from Europe to China. We focus on international business research where studies must seriously consider language to establish a real intercultural dialogue. In a next step, we turn to the Universal Declaration of Human Rights to highlight the ethical issue of translation. Lastly, in line with Jullien’s intercultural approach, we invite scholars in international management to go beyond an implicit Western ethnocentrism based on the concept of identity in order to foster in-context management based on the concept of resource.